New ichnological record from the late campanian Toro Toro Formation at Toro Toro, Potosí (Bolivia): first probable dromaeosaurid tracks from South America - Apesteguía, Sebastián (2011)
Fil: Apesteguía, Sebastián. Consejo Nacional de Investigaciones Científicas y Técnicas. Buenos Aires, Argentina.